A reagentless electrochemical immunosensor for sensitive detection of carcinoembryonic antigen based on the interface with redox probe-modified electron transfer wires and effectively immobilized antibody - Zhang, Jing; Yang, Luoxing; Pei, Jie; Tian, Yanzhang; Liu, Jiyang (Frontiers in Chemistry, 2022)
Convenient and sensitive detection of tumors marked in serum samples is of great significance for the early diagnosis of cancers. Facile fabrication of reagentless electrochemical immunosensor with efficient sensing interface and high sensitivity is still a challenge. Herein, an electrochemical immunosensor was easily fabricated based on the easy fabrication of immunoassay interface with electron transfer wires, confined redox probes, and conveniently immobilized antibodies, which can achieve sensitive and reagentless determination of the tumor marker, carcinoembryonic antigen (CEA). Carboxyl multi-walled carbon nanotubes (MWCNTs) were firstly modified with an electrochemical redox probe, methylene blue (MB), which has redox potentials distinguished from those of redox molecules commonly existing in biological samples (for example, ascorbic acid and uric acid). After the as-prepared MB-modified MWCNT (MWCNT-MB) was coated on the supporting glassy carbon electrode (GCE), the MWCNT-MB/GCE exhibited improved active area and electron transfer property. Polydopamine (PDA) was then in situ synthesized through simple self-polymerization of dopamine, which acts as the bio-linker to covalently immobilize the anti-CEA antibody (Ab). The developed immunosensor could be applied for electrochemical detection of CEA based on the decrease in the redox signal of MB after specific binding of CEA and immobilized Ab. The fabricated immunosensor can achieve sensitive determination of CEA ranging from 10 pg/ml to 100 ng/ml with a limit of detection (LOD) of 0.6 pg/ml. Determination of CEA in human serum samples was also realized with high accuracy.